2020
DOI: 10.3390/ijms21155354
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Transglycosylation Relevant Sites of Cold-Adapted β-d-Galactosidase from Arthrobacter sp. 32cB

Abstract: β-Galactosidase from Arthrobacter sp. 32cB (ArthβDG) is a cold-adapted enzyme able to catalyze hydrolysis of β-d-galactosides and transglycosylation reaction, where galactosyl moiety is being transferred onto an acceptor larger than a water molecule. Mutants of ArthβDG: D207A and E517Q were designed to determine the significance of specific residues and to enable formation of complexes with lactulose and sucrose and to shed light onto the structural basis of the transglycosylation reaction. The catalytic assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For instance, de Maat et al (2019) found that deletion of the lacL gene, encoding the large subunit of the E. faecium b-galactosidase, caused the enzyme to be incapable of digesting the lactose, thus, decreasing the survival of E. faecium. Rutkiewicz et al (2020) found that mutation E517 into glutamine and D207 into alanine could lead to loss of function and a significant drop of activity for b-Galactosidase from Arthrobacter sp. 32cB.…”
Section: Immobilisation Of B-galactosidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, de Maat et al (2019) found that deletion of the lacL gene, encoding the large subunit of the E. faecium b-galactosidase, caused the enzyme to be incapable of digesting the lactose, thus, decreasing the survival of E. faecium. Rutkiewicz et al (2020) found that mutation E517 into glutamine and D207 into alanine could lead to loss of function and a significant drop of activity for b-Galactosidase from Arthrobacter sp. 32cB.…”
Section: Immobilisation Of B-galactosidasesmentioning
confidence: 99%
“…Rutkiewicz et al . (2020) found that mutation E517 into glutamine and D207 into alanine could lead to loss of function and a significant drop of activity for β‐Galactosidase from Arthrobacter sp. 32cB.…”
Section: Genetic Engineering Of β‐Galactosidasesmentioning
confidence: 99%
“…C2-2, Arthrobacter psychrolactophilus strain F2, and other unclassified Arthrobacter spp. were found to produce β-galactosidases, which were active at an optimum temperature range of 0–50 °C [ 88 , 101 , 102 , 103 , 104 ]. As a result of these discoveries, cold-active β-galactosidases produced by A. psychrolactophilus strain F2 are likely suitable enzymes to use under low-temperature conditions due to their activity being highest at 0 °C while their optimum temperature and pH were 10 °C and 8.0, respectively [ 105 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…It is worth noting that recently: (a) a hexameric β-galactosidase has been isolated from the psychrophilic Marinomonas ef1, and has shown remarkable stability against temperature, notwithstanding its highest activity at 5 • C [136]; (b) a dimeric cold-active β-galactosidase has been isolated from Arthrobacter sp. 32cB, and is considered of relevant interest for food industry [137,138].…”
Section: β-Galactosidasementioning
confidence: 99%